From academic silos to interdisciplinary engagement: Understanding and advancing research and evaluation in Sport for Development - Bauer, Katrin; Schulenkorf, Nico; Siefken, Katja (Journal of sport for development, 2024)
Over the last 20 years, the growing recognition of sport as an enabler of sustainable development has allowed Sport for Development (SFD) to emerge as a dynamic research field featuring contributions from a wide range of scholarly disciplines. Within this research, evaluation has played a prominent role, especially against the background of omnipresent demands to ‘prove impact’ and legitimize the field. Despite the growth of scholarly activity, the field remains largely scattered with limited interdisciplinary engagement. This article presents an overview of the conceptualization and implementation of SFD research and evaluation, encompassing study types and methodological approaches. Findings were generated from a scoping review of publications on research and evaluation activities in the SFD field, guided by the newly proposed Evaluation Research Framework. They highlight that the field is suffering from terminological imprecisions that lead to vague and often undifferentiated debates about methodologies and approaches. Moreover, there remains a limited progression of theoretical advancements in SFD, with purposeful engagement across disciplines and innovative developments still being underutilized. We conclude that if SFD scholars remain within their disciplinary silos and do not move towards a common interdisciplinary research understanding, the field will continue to suffer from confusing theorization processes with limited prospects for further academic advancement and practical development.